2023
DOI: 10.1101/2023.03.23.534004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycosylation-modified antigens as a tolerance-inducing vaccine platform prevent anaphylaxis in a pre-clinical model of food allergy

Abstract: The only FDA-approved oral immunotherapy for a food allergy provides protection against accidental exposure to peanuts. However, this therapy often causes discomfort or side effects and requires long-term commitment. Better preventive and therapeutic solutions are urgently needed. We have developed an inverse vaccine technology that utilizes glycopolymer-conjugated antigens to induce antigen-specific non-responsiveness. The glycopolymer conjugates were administered intravenously (i.v.) or subcutaneously (s.c.)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…For in vivo Treg induction study, starting at weaning, Foxp3GFP reporter mice were given drinking water containing a mixture of antibiotics, including ampicillin (1 mg/mL), neomycin (1 mg/mL), metronidazole (0.2 mg/mL), and vancomycin (0.5 mg/mL) (Sigma-Aldrich) starting at weaning. This antibiotic cocktail composition and treatment duration are consistent with standard protocols for depleting microbiota, thus eliminating the influence of endogenous butyrate (57)(58)(59). On day 4 post-weaning, mice were s.c. administered in the abdominal site with saline, NaBut, NtL-ButM, or Neg-ButM at the equivalent butyrate dose of 2.24 mg per mice once a week for three weeks.…”
Section: Treg Induction and Myeloid Cell Suppression Study On Healthy...mentioning
confidence: 73%
“…For in vivo Treg induction study, starting at weaning, Foxp3GFP reporter mice were given drinking water containing a mixture of antibiotics, including ampicillin (1 mg/mL), neomycin (1 mg/mL), metronidazole (0.2 mg/mL), and vancomycin (0.5 mg/mL) (Sigma-Aldrich) starting at weaning. This antibiotic cocktail composition and treatment duration are consistent with standard protocols for depleting microbiota, thus eliminating the influence of endogenous butyrate (57)(58)(59). On day 4 post-weaning, mice were s.c. administered in the abdominal site with saline, NaBut, NtL-ButM, or Neg-ButM at the equivalent butyrate dose of 2.24 mg per mice once a week for three weeks.…”
Section: Treg Induction and Myeloid Cell Suppression Study On Healthy...mentioning
confidence: 73%
“…found that p(Man)-antigen pre-treatment can be used to prevent food allergic responses and reduce antigen-specific IgE as well as IgG. 67 Future work can inform how p(Man) conjugation may impact IgE responses relevant in a minority of ADA responses 68 , 69 and other diseases such as asthma. 70 Since we hypothesize that p(Man)-antigen acts through the abrogation of T cell help, it may not be able to reduce T cell -independent antibody responses, and further work should be done to investigate this application.…”
Section: Discussionmentioning
confidence: 98%
“…With further validation, it may be used in combination with adeno-associated viral vectors to prevent ADAs and allow re-dosing 65 . In other studies, Cao et al found that p(Man)-antigen pretreatment can be used to prevent food allergic responses and reduce antigen-specific IgE as well as IgG 66 . Future work can inform how p(Man) conjugation may impact IgE responses relevant in a minority of ADA responses 67,68 and other diseases such as asthma 69 .…”
Section: Discussionmentioning
confidence: 99%